Pengarustamaan Gender Perspektif Ziba Mir-Hosseini Islam dan Gender: Debat Keagamaan Pada Masa Iran Kontemporer - Mutmainah Mutmainah (STAI Syaichona Moh. Cholil Bangkalan, 2016)
The movement of feminism is to seek justice, want to put women in a position that is proportional, equal, and equal with men so that no differences were discriminatory. Departing from the realization that Ziba Mir-Hossemi Iran underlines feminist critical theory from a feminist perspective, as well as re examine its validity through the viewpoint of reality and contemporary gender theory. He did not merely expose the gender bias that exists and inherent in the rules of jurisprudence and various contradictions, but also look at whether the rules reflect the Shari'a justice or whether it indicates the importance of individual and communal a Muslim society. Ziba assess that women have a close connection to the discourse on Islamic law, especially in issues around marriage and family. Ziba reminded that although in the debate fiqh women are not much noise because it is dominated by men who have the power as